2006
DOI: 10.1590/s0101-20612006000200026
|View full text |Cite
|
Sign up to set email alerts
|

Discriminação de sorovares de Salmonella spp. isolados de carcaças de frango por REP e ERIC-PCR e fagotipagem do sorovar Enteriditis

Abstract: RESUMOSalmonelose é a infecção bacteriana de origem alimentar mais freqüente no Paraná, Brasil, e os surtos estão associados, principalmente, ao consumo de ovos, carne de aves e derivados. Os objetivos deste trabalho foram identificar os sorovares de Salmonella isolados de carcaças de frango e caracterizá-los molecularmente por rEP e ErIc-Pcr, assim como identificar os fagotipos de Salmonella Enteriditis. Dos 25 isolados de Salmonella spp. analisados, 18 foram identificados como Enteriditis, 4 como Braenderup,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…Auto-agglutinable Salmonella enterica was isolated from 1 chicken product sample. Alcocer et al (2006), evaluating 25 Salmonella strains obtained from chicken carcasses from four processing plants located in Paraná State, Brazil, found only one auto-agglutinable strain. Other authors have reported the isolation of autoagglutinable strains in chicken fecal samples in Brazil (Salles et al, 2008;Andreatti Filho et al, 2009).…”
Section: Dna Profiles Of Salmonella Spp Isolated From Chicken Producmentioning
confidence: 99%
“…Auto-agglutinable Salmonella enterica was isolated from 1 chicken product sample. Alcocer et al (2006), evaluating 25 Salmonella strains obtained from chicken carcasses from four processing plants located in Paraná State, Brazil, found only one auto-agglutinable strain. Other authors have reported the isolation of autoagglutinable strains in chicken fecal samples in Brazil (Salles et al, 2008;Andreatti Filho et al, 2009).…”
Section: Dna Profiles Of Salmonella Spp Isolated From Chicken Producmentioning
confidence: 99%
“…in broiler carcasses may vary between 0.024 and 85.0%. It is actually an important transmission vehicle of the bacterium (Aloccer et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Salmonella Enteritidis and Salmonella Typhimurium are among the most prevalent in chickens and have great importâmcia to public health (Aloccer et al, 2006;BACK, 2010). From the mid-80's in Europe and after the beginning of the 90s in Brazil, Salmonella Enteritidis has become one of the most prevalent serotypes in cutting and laying birds.…”
Section: Resultsmentioning
confidence: 99%
“…Neste estudo, em quatro mercados foram identificadas Salmonella enterica subspécie enterica a qual tem como "habitat" os animais de sangue quente e são responsáveis pela maioria das salmoneloses humanas (22) . O sorovar Enteritidis tem sido identificado frequentemente em carcaças de frangos (23,24,25) e é o mais comum em infecções em seres humanos (26) . Contudo, essa estirpe não foi encontrada na atual pesquisa.…”
Section: Nosunclassified